The Influence of FDI on GDP in ASEAN Countries with the Corruption Perception Index as a Moderation Variable - M. Nanda Setiawan; Mardyan Nugraha; Agus Waluyo; Rina Rosia (Universitas Muhammadiyah Purwokerto, 2026)
This study is designed to unravel the dynamics of the relationship between Foreign Investment (FDI) and the expansion of economic output in the Southeast Asian region, by placing the Corruption Perception Index (CPI) as a conditioning factor. Through a quantitative approach, this research utilizes secondary data for the period 2014–2024 from ten ASEAN member countries sourced from the World Bank and Transparency International. Econometric estimation was carried out using the Random Effect Model (REM) and Moderated Regression Analysis (MRA) panel data regression methods through EViews software. The results of empirical analysis prove that FDI flows consistently provide positive and significant stimulation in encouraging an increase in Gross Domestic Product (GDP) in the ASEAN region. However, testing the interaction effect showed that the CPI did not have the statistical power to act as a moderation variable, either in strengthening or weakening the elasticity of capital to the macro output. This phenomenon indicates that investment decisions and foreign capital productivity in ASEAN are more dictated by pragmatism, regional comparative advantage, and the presence of special economic zones that are protected by regulations, rather than influenced by fluctuations in the quality of public institutional governance at the national level. The contribution of this study lies in the remapping of regional investment governance, which suggests the importance of strengthening strategic economic zoning in order to maintain investment attractiveness amid local institutional challenges